A SYNTHESIS OF SLOAN-C EFFECTIVE PRACTICES, AUGUST 2005 - Moore, Janet C. (Online Learning, 2005)
To support continuous improvement in the quality, scale and breadth of online education, the Sloan Consortium invites practitioners to share effective practices. This report synthesizes effective practices submitted by Sloan-C members that have been reviewed and are currently listed in Sloan-C Effective Practices online collection at http://www.sloan-c.org/effective.